Predictive Validity of Student Risk Screening Scale for Internalizing and Externalizing Scores in Secondary Schools. (June 2019) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Cantwell, Emily D.; Royer, David J.; Leko, Melinda M.; Schatschneider, Christopher; Menzies, Holly Mariah
In this article, we examined predictive validity of Student Risk Screening Scale for Internalizing and Externalizing (SRSS-IE) scores for use at the middle ( N = 2, 313 from four middle schools) and high ( N = 2, 727 from two high schools) school level. Results indicated middle and high school students with high levels of risk according to fall SRSS-IE scores (particularly those with externalizing behaviors) were likely to have lower grade point averages, fail more courses, have more nurse visits, and spend more time in in-school suspensions compared with students at low risk for externalizing and internalizing behaviors. Education implications, limitations, and future directions are presented.